2010
DOI: 10.2174/1874091x01004010077
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Effects of Vitamin E and C on Placental Oxidative Stress Induced by Nicotine: An In Vitro Evidence

Abstract: There have been a few studies that examined the oxidative stress effects of nicotine during pregnancy and lactation. The adverse effect of prenatal smoking exposure on human fetal development and growth has been a major public health issue. Active or passive smoking during pregnancy can result in a wide variety of adverse outcomes, including intrauterine growth retardation (IUGR), prematurity, stillbirth, and the sudden infant death syndrome. Smoking in pregnancy has also been associated with an increased risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 28 publications
2
36
0
1
Order By: Relevance
“…An increase in the concentration of cotinine was observed in the urine of nonsmokers who live with smokers (Matsukura et al, 1984;Feyerabend et al, 1982), and in the amniotic fluid of nonsmoking pregnant women chronically exposed to tobacco smoke (Andresen et al, 1982;Smith et al, 1982). It has become evident that oxidative stress is one of the most important mechanisms involved in tobacco smoking during pregnancy (Gallo et al, 2010;Lin et al, 2014). Interestingly, according to our multivariate logistic regression analysis, tobacco smoke exposure had no significant impact on 8-oxodG and 15-F2t-IsoP levels in mothers.…”
Section: Discussionmentioning
confidence: 54%
“…An increase in the concentration of cotinine was observed in the urine of nonsmokers who live with smokers (Matsukura et al, 1984;Feyerabend et al, 1982), and in the amniotic fluid of nonsmoking pregnant women chronically exposed to tobacco smoke (Andresen et al, 1982;Smith et al, 1982). It has become evident that oxidative stress is one of the most important mechanisms involved in tobacco smoking during pregnancy (Gallo et al, 2010;Lin et al, 2014). Interestingly, according to our multivariate logistic regression analysis, tobacco smoke exposure had no significant impact on 8-oxodG and 15-F2t-IsoP levels in mothers.…”
Section: Discussionmentioning
confidence: 54%
“…The essential nutrient 'vitamin C' or ascorbic acid (AA) has been shown to scavenge free radicals and it also forms a strong line of defence against the reactive oxygen species (ROS) induced cellular damage (20). Since nicotine induced developmental neurotoxicity is potentially related to the oxidative stress (21), the antioxidant properties of AA is thought to have protective effect against neurotoxicity induced by prenatal exposure to nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…Since nicotine induced developmental neurotoxicity is potentially related to the oxidative stress (21), the antioxidant properties of AA is thought to have protective effect against neurotoxicity induced by prenatal exposure to nicotine. In vitro studies have demonstrated that AA alone or in combination with vitamin E can effectively protect the human placenta against the deleterious effects of oxidative stress induced by nicotine (20). It has also been shown that AA can prevent the adverse effects of prenatal nicotine exposure on offspring pulmonary function (22).…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies for the management of oxidative stress during pregnancy have been suggested including, but not limited to, the use of antioxidants and vitamins E and A [2,15]. Recently, clinical trials in nonpregnant women have shown that the consumption of probiotics can decrease oxidative stress [16,17,18].…”
Section: Introductionmentioning
confidence: 99%